OER Awareness and Use: The Affinity Between Higher Education and K-12 - Blomgren, Constance (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Educators within Higher Education (HE) and K-12 share in the need for high quality educational resources to assist in the pursuit of teaching and learning. Although there are numerous differences between the two levels of education, there are commonalties in the perceptions of the purpose, practical uses, and challenges that abide in the use of Open Educational Resources (OER). Observations made while producing podcasts and videos for OER awareness, use, and championing, form an exposition of the merits of OER for HE and K-12. Benefits include cost-savings in acquiring resources for teaching and learning as well as user-generated content, instructor creativity, and contextualized and responsively timely learning opportunities. Additionally, the teaching culture of K-12 has historically supported the sharing of learning activities and learning resources. At all levels of education, OER awareness requires a deeper understanding of the changes to teaching and learning borne by open educational practices.